Information and Communication Technology, Mobile Devices, and Medical Education. - Rodríguez-Ríos, Andrea; Espinoza-Téllez, Gerardo; Martínez-Ezquerro, José Darío; Rendón-Macías, Mario Enrique (Journal of Medical Systems, 2020)
Information and communication technologies (ICT) are practical and highly available tools. In medical education, ICTs allow physicians to update their knowledge and remember the necessary information within reach of current mobile devices. ICTs as preparation tools for medical education have not been reported for medical students in Mexico. To assess the use of mobile devices as ICTs with medical education purposes, we distributed a questionnaire through an online survey management system to all the medical students (n = 180) from a private university in Mexico City, 100% agreed to participate. We developed a questionnaire based on previous surveys and adapted it to our university. All participants reported possession of an electronic mobile device, and 95% used it regularly for learning purposes. Regardless of the school year, the most frequent usage given to these devices was the search and reading of medical articles, the use of medical calculators, and taking notes. As the levels in career advances, there was a reduction in the use of electronic devices. According to the students, the main barriers towards using mobile devices for learning purposes were both the lack of access to the Internet and permission from the professor to use them. Most medical students use mobile devices for learning purposes, but usage changes during their education. It is convenient to encourage the use of mobile devices and the development of ICT skills as tools for educational purposes rather than banning their use in schools and hospitals.